2013
DOI: 10.3748/wjg.v19.i37.6214
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of HBV reactivation in hematological malignant patients in south Egypt

Abstract: Past infection with HBV is a risk factor for HBV reactivation in Egypt. Mandatory anti-HBc screening prior to chemotherapy in patients with hematological malignancies is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Therefore, the possible effects of vaccination against HBV on S gene variant prevalence can be overlooked in this study. Several studies identified HBV reactivation hepatitis from occult HBV infection, confirmed by molecular analysis [15,32]. Lack of complete distinction between patients with resolved HBV infection from those with occult HBV infection who progressed to HBV reactivation is a limitation of this study.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the possible effects of vaccination against HBV on S gene variant prevalence can be overlooked in this study. Several studies identified HBV reactivation hepatitis from occult HBV infection, confirmed by molecular analysis [15,32]. Lack of complete distinction between patients with resolved HBV infection from those with occult HBV infection who progressed to HBV reactivation is a limitation of this study.…”
Section: Discussionmentioning
confidence: 87%
“…Occult HBV infection was reported in 21% of HCV-infected Egyptian children with hematological disorders and malignancies with liability for reactivation. There is preliminary evidence that immuno-compromised patients are more susceptible to lower infectious doses and are at a higher risk of developing chronic infections [29][30][31][32].…”
Section: Discussionmentioning
confidence: 98%
“…A precore stop mutation (A1896) was detected in one patient with genotype Bj who developed fulminant liver failure [63] . Also sub-genotype D1 has been described as possibly associated with HBV reactivation in two studies, one from Egypt and one from Italy [21,64] . There is general agreement for the use of nucleos(t)ide analogues to prevent HBV reactivation in HBsAgpositive immunosuppressed patients, whereas it is still a matter of debate whether subjects with occult HBV infection should be treated or closely monitored for early treatment once HBsAg positivity has developed.…”
Section: Immunosuppressionmentioning
confidence: 99%